Quality characteristics in rapeseed-mustard and role of some anti-nutritional factors in plant defense: future strategies (Journal of Oilseed Brassica, 2026)
Recommendations for use of rapeseed-mustard oil and seed meal for consumption purposes particularly presence of low saturated fat, high oleic acid, balanced ratio of SFA/MUFA/PUFA and antioxidants, and absence of trans-fat and minimum anti-nutritional factors, are generally different from those of industrial requirements. Further, some anti-nutritional factors present in rapeseed-mustard crops are known to be associated with some plant defense system and other important biological functions. These factors have brought the crop quality research on top with the objective of producing designer crops specific for consumption and industrial purposes. For producing such designer crops through conventional breeding, screening of the available germplasm for specific traits and their further utilization in crop improvement programme becomes necessary. An integrated approach including plant breeding, genetics, biochemistry and biotechnology including bioinformatics is essential in identifying new related biomarkers, or elucidating the chemistry of regulation of various biotic and abiotic stresses. In the present review, information regarding rapeseed-mustard quality characteristics and on correlation of some anti-nutritional factors with some biotic and abiotic stresses has been compiled.